Comparing the yield of maize (Zea mays L.) hybrids in organic and conventional agriculture - Áldott-Sipos, Ágnes; Csepregi-Heilmann, Eszter; Spitkó, Tamás; Szőke, Csaba; Pintér, János; Berzy, Tamás; Nagy, János; Marton, Csaba L. (Acta Agraria Debreceniensis, 2023)
The European Green Deal was published by the European Commission in 2019. The main aim of the program is to reach net zero greenhouse gas emissions by 2050, making Europe the first climate-neutral continent in the world. To achieve this, criteria are also set for agriculture: increasing the share of land under organic farming to 25%, reducing the use of fertilisers and pesticides. However, the benefits of organic farming are widely debated. The aim of our study was to compare the yield of maize (Zea mays L.) hybrids bred in Martonvasar in two different cropping environments. The silage yields of 20 different maize hybrids were evaluated in a three replicate small plot experiment in an organic field and an adjacent conventional field. The average green mass yield of the hybrids was 36,58 t ha-1 in the organic field and 43,03 t ha-1 in the conventional. The green mass yield in the organic area was 20% lower than in the conventional area, and the dry matter yield and digestible dry matter yield were about 18% lower. Hybrids of different maturity groups responded differently to organic cultivation. The yields of early hybrids decreased more and late hybrids less in the organic farming compared to the conventional production.